PENGARUH LINGKUNGAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. MULTAZAM SUKSES BERJAMA’AH - Priniansyah, Nabilah Tirta; Murniyati, Murniyati (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
PT. Multazam Sukses Berjama’ah Sukabumi is a company engaged in the textile industry. The company provides finished fabric materials with various offered patterns that can then be sold on the market and further processed into clothing. The length of the fabric sold can be adjusted according to the buyer’s request. This thesis research aims to analyze and determine whether there is an influence of the work environment and work motivation on employee performance at PT. Multazam Sukses Berjama’ah Sukabumi, both partially and simultaneously. The type of research used is quantitative research. The data collection methods used in this thesis are questionnaires, interviews, observation, and literature study. The data obtained through the questionnaires used a Likert scale measurement. The research sample consisted of 45 employees using the saturated sampling technique. The analysis used includes T-test and F-test hypotheses testing with the assistance of SPSS 25 software. Based on the results obtained, the work environment and work motivation significantly influence employee performance both partially and simultaneously.